Micro flora of Bile Aspirates in Symptomatic Cholelithiasis - Zafar Iqbal Malik, M.A.Nasir Malik, Omer Salahuddin, Muhammad Azhar, Omer Dilawar (Journal of Rawalpindi Medical College, 2009)
Background: To determine the frequency of microbial flora and their antibiotic susceptibility patterns in patients with symptomatic cholelithiasis. Methods: This descriptive study was conducted in Surgical Unit - II, POF Hospital Wah Cantt from June 2007 to June 2008. One hundred cases of cholelithiasis, selected and operated by open cholecystectomy were included in this prospective non-interventional study. Inclusion criteria were patients operated for symptomatic cholelithiasis. Patients with acute cholecystitis, history of jaundice, choledocholithiasis and or dilated common bile duct were excluded from the study. Bile samples were collected from the gallbladder at the time of operation. Age and sex were also noted. The results were recoded on a proforma. Approval was taken from our own ethical committee. Results: Out of 100, 32 patients had positive bile culture from gallbladder. The most common organism was Escherichia. coli (14 patients) followed by Proteus (8), Pseudomonas (4), Staphylococcus aureus (2), Streptococcus (2) and Anaerobes (2). Most of the biliary organisms were highly sensitive to the 3rd generation cephalosporins. Conclusion: The importance of obtaining cultures of bile at the time of cholecystectomy lies in the fact that appropriate antibiotic can be administered in the event of positive culture to forestall serious complications like gram negative septicaemia